SUBSAMPLING AN AUDIT CONTROL TOOL - علي خليفة (Dirasat in Economics and Business, 1975)
Statistical sampling has been widely recognized as a useful audit tool. A good portion of the accounting literature has been devoted to this subject(l). However, the use of statistical sampling in auditing has been limited to the testing of and drawing conclusions about the client's populations ; i.e., accounts receivable, inventory, etc. That is, the generally accepted purpose of statistical sampling in auditing has been to test the accuracy of the work and rcpresentations of the client and his employees. This article l)resents another potential use of statistical sampling by the auditor ; namely, testing the work of his staff accountants.